The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1186/1756-8935-6-21
|View full text |Cite
|
Sign up to set email alerts
|

Functional impact of Aurora A-mediated phosphorylation of HP1γ at serine 83 during cell cycle progression

Abstract: BackgroundPrevious elegant studies performed in the fission yeast Schizosaccharomyces pombe have identified a requirement for heterochromatin protein 1 (HP1) for spindle pole formation and appropriate cell division. In mammalian cells, HP1γ has been implicated in both somatic and germ cell proliferation. High levels of HP1γ protein associate with enhanced cell proliferation and oncogenesis, while its genetic inactivation results in meiotic and mitotic failure. However, the regulation of HP1γ by kinases, critic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(37 citation statements)
references
References 47 publications
2
35
0
Order By: Relevance
“…An enhanced effect of the combination to inhibit PDAC growth is also observed with 3D spheroid and organoid cultures, as well as xenografts in vivo (Figure 3). This is consistent with the fact that these targets are in the same biological pathway that aids to the proper completion of mitosis [12]. Upon cell cycle arrest caused by AurkA inhibition, the mitotic machinery is exposed longer to targeting by the H3K9me pathway, which during mitosis regulates centromere structure.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…An enhanced effect of the combination to inhibit PDAC growth is also observed with 3D spheroid and organoid cultures, as well as xenografts in vivo (Figure 3). This is consistent with the fact that these targets are in the same biological pathway that aids to the proper completion of mitosis [12]. Upon cell cycle arrest caused by AurkA inhibition, the mitotic machinery is exposed longer to targeting by the H3K9me pathway, which during mitosis regulates centromere structure.…”
Section: Discussionsupporting
confidence: 75%
“…Western blots were performed as previously described [12]. Membranes were blocked in 3% BSA/TBST and incubated overnight at 4°C with primary antibody (Supplementary Table 1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reports have detected high levels of HP1γ protein associated with enhanced cell proliferation and oncogenesis in colon, breast, and cervical cancers (Takanashi et al , ; Abe et al , ; Slezak et al , ). Also, HP1γ S83 was reported enriched at the mitotic spindle, suggesting an additional role in proper mitotic cell division (Grzenda et al , ). Our in vivo analysis indicated that terminally differentiated columnar absorptive enterocytes were devoid of HP1γ, while the expression was detectable in the basal level of the crypt that contained the proliferative cell compartment.…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed that HP1α localizes to heterochromatin by binding to the tri-methylated tails of histone H3 at Lysine 9 (H3K9me3). [26][27][28] It has also been shown that Aurora B-mediated phosphorylation of the adjacent H3 serine 10 residues displaces HP1 binding from mitotic heterochromatin and forms part of a binary "methyl/phospho" switch that is critical for proper cell division in yeast 29 and mammalian cells. 30 In mammals, recruitment of the AuroB/AIM-1 kinase complex to HP1α sites in heterochromatin is reported to occur in G 2 and is important for the G 2 /M transition.…”
Section: Changes In Hp1α Dynamics In Escsmentioning
confidence: 99%